SÍNTESE E CARACTERIZAÇÃO DE SISTEMAS NANOESTRUTURADOS PARA FOTOELETROCATÁLISE - Marques, José Francisco Zavaglia (2014)
The photocatalytic and photoelectrochemical degradation of Rhodamine 6G dye was studied using TiO2 , TiO2 doped with N , TiO2 thin films prepared by thermal decomposition of polymeric precursors and titanates prepared by hydrothermal synthesis method. The materials synthesized by thermal decomposition of polymeric precursor method were heat-treated at 450 ° C and in the hydrothermal synthesis TiO2 in anatase phase in 40 g / L NaOH at 20 bar was thermally treated at 200 ° C. The obtained compounds were characterized by X- ray diffraction, nitrogen adsorption using the BET method and the morphology was observed by using atomic force microscopy and scanning electron microscopy. The results demonstrate that the obtaining nanostructures are titanium dioxide in the pure anatase phase and titanates, with specific areas ranging from 45 to 63 m2/g for TiO2 and 120 to 510 m2/g for titanates. Adsorption tests were performed to determine the equilibrium parameters and with the photocatalytic tests the kinetic parameters were determined. The adsorption capacity was correlated with the specific area and TiO2 in the anatase phase exhibits the higher efficiency for dye degradation and in removal of total organic carbon. The galvanostatic method with the TiO2 electrode illuminated with UV radiation shows higher degradation rate and higher removal of total organic carbon.